Religious Moderation in the Social-Religious Practices of Muhammadiyah and Nahdlatul Ulama in Mulyoagung Village, Malang, Indonesia - Firmansah, Dedy (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
This study examines the understanding and implementation of religious moderation among Muhammadiyah and Nahdlatul Ulama (NU) members in Mulyoagung Village, Malang Regency. Using a qualitative research method with a case study approach, this research explores how these two Islamic organizations, despite their theological differences, engage in intergroup cooperation and foster social harmony. Data were collected through in-depth interviews and direct observations, focusing on how religious moderation is perceived and practiced in everyday life. The findings reveal that both Muhammadiyah and NU members exhibit a strong commitment to religious moderation, which is reflected in their inclusive and collaborative social and religious activities. Muhammadiyah, through its Islam Berkemajuan framework, emphasizes progressiveness, rationality, and openness, while NU, through Islam Nusantara, integrates Islamic teachings with local traditions to promote tolerance and balance. These principles enable both groups to maintain a peaceful coexistence, engage in joint community programs, and uphold mutual respect. This study confirms that religious differences do not necessarily lead to conflict; instead, they can serve as a foundation for cooperation when approached with openness and inclusivity. The findings offer a model of religious moderation that can be applied in other pluralistic communities, contributing to broader discussions on intergroup harmony in contemporary society.